Ladder- and bridge-like polynorbornenes with phosphate linkers: facile one-pot synthesis and excellent properties1. Issue 100 (29th October 2015) - Ding, Liang; Zhang, Junmei; Wang, Lingfang; Wang, Chengshuang
<x xml:space="preserve">Abstract</x> A novel telechelic double-stranded polymer with two terminal alkenyl groups was prepared through ROMP of the corresponding monomer bearing a phosphate linker, and was then used as a macromonomer in ADMET polymerization to yield a bridge-like polymer.